1869 Minn. Gen. Laws 50-51 - (:unkn) unknown (My University, 1869)
Ch. 39, §§ 1-3: Prohibited the setting of a trap gun or spring gun, pistol, or other deadly weapon. Violators punished not less than six months in jail or fine not exceeding five hundred dollars or both if there is no injury. If death results, imprisonment not less than ten but no more than fifteen years. If injury results, punishable by imprisonment not exceeding five years.
Keywords: TRAP GUNS